Advancements in Adjuvanticity of Bioactive Inorganic and Organic Compounds - Banerjee, Jhimli; Dey, Sananda; Ali, Kazi M.; Giri, Biplab; Dash, Sandeep Kumar (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Regardless of the enormous success of vaccines over decades, the formulation of biocompatible and highly effective vaccines is still insufficient for combating new pathogens. Discussion: The degree of effectiveness of any vaccine largely depends on the choice of appropriate adjuvant. Along with the optimum biocompatibility, an ideal adjuvant must be biodegradable, economical and easy to manufacture. To date, various organic and inorganic substances have been used as an adjuvant to augment the effectiveness of the vaccine. Immunological adjuvants are essential for strong and long-term effects against various pathogens. However, a very limited number of licensed adjuvants are available for the formulation of a successful vaccine. This leads to a challenging situation in medical science. Conclusion: The present review concisely summarizes the mechanism of action of various bioactive organic and inorganic immunological adjuvants, their limitations and future perspectives for their appropriate modification. Current trends of anticancer therapies using immunological adjuvants have also been highlighted in this review.
Keywords: Adjuvant